Cs2Zn5(PO4)4 and Cs3La(PO4)2: Two Cs‐Containing Phosphates with Three‐Dimensional Frameworks. Issue 19 (8th May 2019) - Guo, Fengjiao; Han, Jian; Cheng, Jianian; Yang, Zhihua; Abudouwufu, Tushagu; Yu, Hongwei; Pan, Shilie
Abstract : Two phosphates, Cs2 Zn5 (PO4 )4 and Cs3 La(PO4 )2 have been successfully synthesized by employing the conventional solid‐state reaction method, and their structures were determined by single‐crystal X‐ray diffraction. Cs2 Zn5 (PO4 )4 owns a three‐dimensional∞ 3 [Zn4 P4 O16 ] framework and Cs3 La(PO4 )2 features∞ 2 [La3 P6 O29 ] layers spreading in the bc plane. Infrared spectroscopy, UV/Vis‐NIR diffuse reflectance spectroscopy were performed. The thermal properties and electronic structures of two compounds were investigated. In addition, the Ce 3+ doped Cs3 La(PO4 )2 phosphor was synthesized and its photoluminescence was analyzed. The results indicate that the Cs2 Zn5 (PO4 )4 :0.01Ce 3+ phosphor can be excited by ultraviolet light to obtain blue luminescence. Abstract : Two Cs‐containing phosphates Cs2 Zn5 (PO4 )4 and Cs3 La(PO4 )2 feature three‐dimensional (3D) frameworks constructed by∞ 3 [Zn4 P4 O16 ]/CsOn and∞ 2 [La3 P6 O29 ]/CsOn, respectively. Both of them have wide transmission windows with ultraviolet absorption edges. The Ce 3+ doped Cs3 La(PO4 )2 phosphor can be excited by ultraviolet light to obtain a blue luminescence.